-2+{-9-[(-6)+(11)+5]x5}+43=
Răspunsuri la întrebare
Răspuns de
1
Salut! =)
-2 + { -9 - [( -6 ) + 11 + 5 ] × 5 } + 43
-6 + 11 + 5 = -6 + 16 = 10
- 9 - 10 × 5 = - 9 - 50 = -59
- 2 + ( - 59 ) + 43
- 2 - 59 + 43 = - 61 + 43 = -18
Bafta! =)
Răspuns de
2
Răspuns:
Explicație pas cu pas:
= -2+{[ -9- [ (-6+11+5) ] x5 } +43
= -2 + [ -9 -( 10x5)] +43
= -2 +(-9-50)+43
=-2 -59+43
= -61+43
= - 18
Alte întrebări interesante
Matematică,
8 ani în urmă
Matematică,
8 ani în urmă
Matematică,
8 ani în urmă
Matematică,
8 ani în urmă
Matematică,
8 ani în urmă
Limba română,
9 ani în urmă
Limba română,
9 ani în urmă